PENGARUH MEDIA GOOGLE SLIDES KONTEKSTUAL TERHADAP KEMAMPUAN EKOLITERASI PADA MATERI FIQIH KELAS X DI MA HASYIMIYAH - Ni’ matul Maula (JIP: Jurnal Ilmu Pendidikan, 2025)
This study aims to analyze the influence of contextual Google Slides media on students’ ecoliteracy skills in learning Fiqh for Grade X at MA Hasyimiyah. The rapid development of digital technology in education requires teachers to utilize interactive and contextual learning media that can enhance students’ understanding and environmental awareness. Google Slides, when integrated with contextual learning principles, provides visual, relevant, and real-life examples that help students connect Fiqh concepts with environmental values. This study aims to analyze the influence of contextual Google Slides media on students’ ecoliteracy skills in learning Fiqh for Grade X at MA Hasyimiyah. The rapid development of digital technology in education requires teachers to utilize interactive and contextual learning media that can enhance students’ understanding and environmental awareness. Google Slides, when integrated with contextual learning principles, provides visual, relevant, and real-life examples that help students connect Fiqh concepts with environmental values.  The findings indicate that students who were taught using contextual Google Slides showed a significant improvement in their ecoliteracy skills compared to those taught through traditional methods. The media effectively enhanced students’ understanding of Fiqh materials related to environmental ethics, cleanliness, and responsible behavior based on Islamic principles. The integration of contextual visual elements strengthened students’ ability to connect religious teachings with real-world environmental issues. In conclusion, contextual Google Slides media has a positive and significant influence on improving ecoliteracy skills in Fiqh learning. This study suggests that teachers incorporate technology-enhanced and contextualized learning media to foster deeper comprehension and environmental awareness among students. The results provide valuable insights for developing innovative instructional strategies in Islamic education.